Population Density, Reproduction Cycle and Nutritional Value of Sphaerechinus granularis (Echinodermata: Echinoidea) in an Oceanic Insular Ecosystem - Lourenço, Sílvia; José, Ricardo; Neves, Pedro; Góis, André; Cordeiro, Nereida; Andrade, Carlos; Ribeiro, Cláudia (Frontiers in Marine Science, 2022)
Sea urchins play an important role in island coastal ecosystems as keystone species and as potential resources for harvesting and aquaculture. In Southern Europe, the most valuable and harvested species is the European purple sea urchin Paracentrotus lividus, but there is a growing interest to explore other edible species like the blunt sea urchin Sphaerechinus granularis. The echinoderms biodiversity of Madeira archipelago was previously described, but their local habitat, population densities and size distribution, important to establish their harvest and aquaculture potential, are poorly known. The present study aimed to evaluate S. granularis population in the oligotrophic and narrow insular shelf of Madeira archipelago, mainly regarding its habitat, densities, reproduction season and roe marketable characteristics. Sphaerechinus granularis was found in low densities (0.01 ind./m2) from shallow to deep reefs (5–30 m). The highest densities occurred in shallow waters and breakwaters in association to encrusting algae, turf and erect brown macroalgae. Here, the low primary productivity ecosystem influenced the long reproductive season of the local population. This population showed a relatively high gonadosomatic index (maximum GI of 8), high gonad weight (5.00–12.19 g) with high proportion of bright yellow and orange gonads (37.5–60%) between February and November. Additionally, the high level of total carotenoids, the high PUFA (particularly EPA) content, and the ratio n-6/n-3 close to one support the high nutritional value of S. granularis roe. The trend of incremental GI between September and November and the increasing content of PUFA in autumn suggests this could be the preferential harvesting season. This information is key to evaluate a sustainable exploitation of this living marine resource.